Propuesta para el diseño de una planta de tratamiento de aguas residuales empleando métodos físicos y biológicos combinados en el camal municipal del cantón Zamora - Cabrera Delgado, Luis Alejandro (2016)
The present titling work was carried out with the objective of evaluating the current system of the wastewater treatment plant and designing an alternative proposal using combined physical and biological methods that contribute to the decontamination of the wastewater generated in the different activities Of the processes of slaughtering inside the municipal camal of the canton Zamora. In this proposal, the literature review was taken into account in order to take into account basic concepts of research related to the subject of study, and the methodology used in this proposal is established to perform the respective diagnosis of the current system of the plant Wastewater treatment, which consisted of interviews, direct observations and the respective characterization of the residual water in order to know the different problems that are generated in the study site, and also the current state of the residual water produced by the Activities carried out within the camal facility, resulting in a flow rate of 0.11 l / s per day, and in the same way it was analyzed that the parameters established in Ministerial Agreement 028 of Table 12 exceed the limits of discharge to A body of fresh water from table 10. Next, a proposal for a new design for the treatment of wastewater used combined physical and biological methods was carried out in the municipal road of the Zamora canton, which was carried out using formulas and criteria established in the Urban Waste Water Treatment Manual and The Standards for the Study and Design of Drinking Water Systems and Disposal of Wastewater for Populations greater than 1000 inhabitants, and also the results obtained in the characterization of the waste water were taken into account. Finally it can be concluded that in the present research work, the current wastewater treatment plant is not functioning properly so it is very important to present this proposal to the Autonomous Municipal Decentralized Government of Zamora